A single migrant enhances the genetic diversity of an inbred puma population. Issue 5 (24th May 2017) - Gustafson, Kyle D.; Vickers, T. Winston; Boyce, Walter M.; Ernest, Holly B.
Abstract : Migration is essential for maintaining genetic diversity among populations, and pumas ( Puma concolor ) provide an excellent model for studying the genetic impacts of migrants on populations isolated by increasing human development. In densely populated southern California, USA, puma populations on the east and west side of interstate highway 15 (I-15) have become fragmented into a small inbred population on the west side (Santa Ana Mountains) and a relatively larger, more diverse population on the east side (Eastern Peninsular Range). From 146 sampled pumas, genetic analyses indicate seven pumas crossed I-15 over the last 15 years, including four males from west to east, and three males from east to west. However, only a single migrant (named M86) was detected to have produced offspring and contribute to gene flow across the I-15 barrier . Prior to the M86 migration, the Santa Ana population exhibited inbreeding and had significantly lower genetic diversity than the Eastern Peninsular Range population. After M86 emigrated, he sired 11 offspring with Santa Ana females, decreasing inbreeding measures and raising heterozygosity to levels similar to pumas in the Eastern Peninsular Range. The emigration of M86 also introduced new alleles into the Santa Ana population, although allelic richness still remained significantly lower than the Eastern Peninsular population. Our results clearly show the benefit of a single migrant to the genetics of a small, isolated population. However, ongoing development and habitat loss on both sides of I-15 will increasingly strengthen the barrier to successful migration. Further monitoring, and potential human intervention, including minimizing development effects on connectivity, adding or improving freeway crossing structures, or animal translocation, may be needed to ensure adequate gene flow and long-term persistence of the Santa Ana puma population.